Big Five Personality on Life Satisfaction: Job Satisfaction and Job Stress as Mediators (Study on Small Enterprises in Garut Regency) - Kosasih, Kosasih; Yuliaty, Farida; Paramarta, Vip; Kania, Dewi; Fitriana, Fitriana (Universitas Mercu Buana, 2024)
Objective: The purpose of this study is to investigate the relationship between personality traits and life satisfaction, as well as the impact of job satisfaction on life satisfaction and work stress. While investigating the function of job stress and job satisfaction in mediating the link between these variables.Methodology: This specific field of study adopts a quantitative research methodology and survey research techniques. A multivariate statistical method is used in the statistical tool that uses SmartPls 4 v.4.0.9.4 to compare exogenous and endogenous factors. The number of micro-enterprises in Garut Regency reached 150.557 (Garut Cooperative and SMEs Office, 2019), absorbing a total workforce of 2953 people. So, the population is the SME workforce who are still actively working. Sampling using incidental sampling and Purposive or Judgment sampling, namely sampling based on the number of respondents who filled out the instrument and must follow the sample proportions required in the SEM-SmartPlsmodel. So, the minimum sample is 120 employee respondents. Incidental sampling can likely achieve more than 130.Findings: According to the findings of hypothesis testing using Smart PLS, the first hypothesis (H1) is accepted, implying that personality significantly affects work stress. Since the second hypothesis (H2) is confirmed, personality affects life satisfaction. The third hypothesis (H3) is accepted which means that there is a significant relationship between job satisfaction and work stress. The fourth hypothesis (H4) is not accepted, proving that there is no discernible relationship between job happiness and life satisfaction. The fifth hypothesis (H5) is accepted which suggests that life satisfaction is significantly impacted by work stress. H9 is rejected, although H6, H7, and H8 are accepted.Conclusion: The capacity to forecast life satisfaction which falls into the moderate group can be attributed to the Big Five personality, job contentment, and work stress. Employees of SMEs in the Garut Regency can become more satisfied at work and in general by changing their personalities. Employees of SMEs experience both distress and eustress because job satisfaction has a favorable and important effect on work stress. It has not been demonstrated that life satisfaction is significantly influenced by job satisfaction. Life satisfaction is significantly impacted by job stress, suggesting that this stress is pleasant (eustress), such as self-motivation and stimulation to achieve personal goals in the work and life domains. According to mediation tests, the effect of personality on work stress is mediated by job satisfaction.